Stop the Bleed®: Medical Students as Instructors of the Bleeding Control Basics Course. Issue 2 (February 2023) - Evans, Kelsey M.; Lake, Bryan; Harrell, Kelly M.; Longshore, Shannon W.; Toschlog, Eric A.; Walsh, Danielle S.
Background: The Bleeding Control Basics (B-Con) Course was developed to teach lifesaving hemorrhage control techniques to the public. Currently, medical students (MS) without prior clinical experience (CE) may not act as autonomous instructors, limiting the instructor pool. Purpose: To assess the bleeding control knowledge of MS (phase I) and compare the knowledge of students taught by a certified instructor vs a medical student (phase II). Methods: Phase I: 20 MS, 6 with prior CE and 14 without clinical experience (NCE) completed a pre-course and post-course knowledge assessment. Results were assessed by independent sample t-tests. Phase II: 91 first-year MS were taught the B-Con Course by either a third-year MS (n = 45) or certified instructor (n = 46). An analysis of covariance (ANCOVA) was performed to compare scores by instructor type (certified vs MS) using prior CE and pretest scores as confounding variables. Results: In Phase I, the CE group scored higher on the pretest assessment compared to the NCE group ( P = .003). All students improved in posttest scoring, and there was no difference in posttest scores between the groups ( P = .597). In Phase II, despite no difference in pretest scores between groups, the MS taught learners scored significantly higher on the posttest compared to the certified instructor group ( P < .01). Prior CE did not correlate to posttest scores ( P = .719). Discussion: Medical students are as effective as certified instructors at conveying the B-Con learning objectives. Based on near-perfect assimilation of content by students, MS should be permitted to teach B-Con Courses.